Climate change: Vulnerability and resilience of tourism and the entire economy. (June 2019) - Dogru, Tarik; Marchio, Elizabeth A.; Bulut, Umit; Suess, Courtney
Abstract: Fluctuating and extreme weather patterns are acute indicators of climate change and these patterns modify tourist activities. The tourism industry is thus considered highly vulnerable to climate change. However, the effects of climate change on tourism have not yet been extensively quantified. Furthermore, the extent to which tourism is vulnerable or resilient to climate change has not been compared to other sectors of the economy. This study examines the extent to which vulnerability and resilience to climate change affect tourism and the overall economy. The results indicate the effects of vulnerability are much greater than those of resilience. The tourism industry is more vulnerable, yet more resilient, to climate change compared to the overall economy. The strength of these effects varies across countries with different income levels: countries with the lowest income levels are more vulnerable and less resilient, and those with the highest income are the least vulnerable and most resilient. Highlights: Tourism industry's vulnerability and resilience to climate change is conceptualized and quantified. Tourism industry is highly vulnerable to climate change but it also shows some resilience. Tourism industry is more vulnerable to climate change than the entire economy. Tourism industry and the entire economy is equally resilient to climate change. Countries with the lowest income levels are more vulnerable and less resilient.